Emerging chiral edge states from the confinement of a magnetic Weyl semimetal in Co3Sn2 S2 - Muechler, Lukas; Liu, Enke; Gayles, Jacob; Xu, Qiunan; Felser, Claudia; Sun, Yan (Physical Review B, 2020)
The quantum anomalous Hall effect (QAHE) and magnetic Weyl semimetals (WSMs) are topological states induced by intrinsic magnetic moments and spin-orbit coupling. Their similarity suggests the possibility of achieving the QAHE by dimensional confinement of a magnetic WSM along one direction. In this paper, we investigate the emergence of the QAHE in the two-dimensional (2D) limit of magnetic WSMs due to finite-size effects in thin films and step edges. We demonstrate the feasibility of this approach with effective models and real materials. To this end, we have chosen the layered magnetic WSM Co3Sn2S2, which features a large anomalous Hall conductivity and anomalous Hall angle in its three-dimensional bulk as our material candidate. In the 2D limit of Co3Sn2S2, two QAHE states exist depending on the stoichiometry of the 2D layer. One is a semimetal with a Chern number of 6, and the other is an insulator with a Chern number of 3. The latter has a band gap of 0.05 eV, which is much larger than that in magnetically doped topological insulators. Our findings naturally explain the existence of chiral states in step edges of bulk Co3Sn2S2 which have been reported in a recent experiment at T=4K and present a realistic avenue to realize QAH states in thin films of magnetic WSMs.
CRIS-Team Scopus Importer:2022-04-14